MOTIVASI PENGGUNAAN MEDIA SOSIAL INSTAGRAM DI KALANGAN MAHASISWA HUBUNGAN MASYRAKAT UNIVERSITAS KRISTEN SATYA WACANA SALATIGA - Herwin Togar Parulian Manik; Richard Gordon Mayopu (PAX HUMANA, 2018)
This research was conducted at the Information Technology Faculty because based on the analysis of the tag metadata used on Instagram social networks, there were more than the other faculties at Satya Wacana Christian University, which were 5,444 posts as of October 26, 2018. The research method used was explorative for provide an explanation of the topics used in the study. Data analysis in qualitative research was carried out before entering the research arena. The results showed that the success of SWCU Public Relations students interpreting instagram can be seen from the reasonableness of individuals that can be accepted by the social environment. Student life in real life and Instagram media are sometimes not compatible but all judgments about positive and negative impacts are determined by each individual. This research answers Bell's (2001) social simulation theory which shows that the meaning of Instagram for SWCU Public Relations students is a tool for behaving to adjust the demands of technology through social media.